The influence of social media marketing activities on hotel brand loyalty: The mediating role of customer engagement and brand trust on the Tiktok - Yudha, Aji; Lestari, Lela; Yasmin, Annisa (Diponegoro International Journal of Business, 2025)
TikTok’s emergence as a social media platform has significantly influenced marketing strategies. Nevertheless, scholarly research on the use of TikTok as a marketing medium remains scarce. Consequently, this study investigates the impact of social media marketing activities on TikTok on brand loyalty, with customer engagement and brand trust serving as mediating factors. This study employs a quantitative research design, utilizing a sample of 300 respondents who actively engaged with the selected hotel on TikTok and stayed at the hotel within the past year. Data were collected through the distribution of a closed-ended questionnaire administered online. Data analysis was conducted using the SEM GSCA Pro. Mediation analysis was performed using the Sobel test. The results demonstrate that social media marketing activities positively influence customer engagement and brand trust. Customer engagement positively affects brand trust and brand loyalty, and brand trust also positively impacts brand loyalty. Additionally, the mediation analysis indicates that customer engagement mediates the relationship between social media marketing activities and brand trust and loyalty. Similarly, brand trust mediates the effect of social media marketing activities on brand loyalty, as well as the effect of customer engagement on brand loyalty. This study contributes to the development of the Stimulus–Organism–Response (SOR) Theory by integrating social media marketing activities with brand loyalty, mediated by customer engagement and brand trust within the hotel industry. Furthermore, this study offers theoretical novelty by applying the SOR framework to emerging tourism regions, demonstrating its relevance in explaining consumer behavior in digital marketing contexts characterized by dynamic but regionally limited markets.